Impacts on reproduction of Enchytraeus crypticus in fertilized soils with chicken litter treated with synthetic and natural insecticide - Testa M.* (2020)
© 2020Poultry litter is used as a fertilizer due to the high concentration of nutrients. However, this material receives application of medicines, whether they are used to treat animals or the litter itself. Thus, the objective was to evaluate if the application in soils of poultry litter doses treated with two insecticides (cypermethrin and cinnamon oil) used to control of the Alphitobius diaperinus, affect the reproduction of Enchytraeus crypticus, and the insecticides effects over time, trough of ecotoxicological tests using soils with different textural classes an Entisol and an Oxisol. In the Oxisol the application of poultry litter stimulated the E. crypticus reproduction regardless of the insecticide and the collection time. In Entisol the poultry litter showed a toxicity at 10 t ha−1 when treated with cypermethrin and at 30 t ha−1 with cinnamon oil. Entisol results show that cypermethrin affects non-target edaphic organisms soon after spraying, but over time has reduced toxicity unlike cinnamon oil.